Can theory of mind be improved? Positive expectations cause better theory of mind performance in a community sample. (December 2020) - Dorn, Laura M.-L.; Rief, Winfried; Mehl, Stephanie
Abstract: Background and objectives: Theory of Mind (ToM) deficits are present in several mental disorders and closely related to problems in social functioning and lower quality of life. While several trainings are aimed at improving ToM performance, it is unknown whether positive expectations on a persons' ToM performance might cause better ToM achievement. Methods: Participants ( n  = 131) first completed a mock ToM test and were then randomly assigned to either receive standardized positive, negative or no feedback on their ToM performance. Secondly, their expectations on their own ToM performance were assessed. Thirdly, ToM was assessed using the Movie Task for the Assessment of Social Cognition (MASC). Results: Participants who received positive feedback resulted in positive expectations on their ToM performance and showed enhanced ToM performance, whereas negative feedback did not lead to negative expectations and negative expectations did not affect a change in ToM performance. Limitations: In the present exploratory study, the effect of positive expectations on ToM performance was assessed in a community sample. Thus, the study should be replicated in a clinical sample for more in-depth results. Conclusions: ToM performance could be enhanced by inducing positive expectations on one's ToM performance, whereas negative feedback had no effect. The present study suggest that interventions that focus on strengthening positive expectations on one's ToM performance could enhance the efficacy of present ToM training methods. Highlights: Positive feedback resulted in positive expectations on Theory of Mind performance. Positive expectations led to improved ToM performance in a community sample. Negative feedback did not result in negative expectations. Performance expectations did not mediate the effect of feedback on ToM performance. Theory of Mind performance could be enhanced by inducing positive expectations.